2013
DOI: 10.1177/000348941312201106
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Facial Nerve Function in Irradiated and Nonirradiated Nerve Grafts

Abstract: In the present series, 45% of patients had an HB grade of III or IV at long-term follow-up. The best outcome (HB grade III) was observed after cross-facial grafting with the sural nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Although the reasons underlying individual patients’ choice were complex and multifactorial, some did not want further open surgery for fear of surgical complications, unpredictability of results and prolonged recovery . In addition, an internal review demonstrated poorer clinimetric outcomes following facial nerve grafting in patients who went on to receive postoperative radiotherapy as part of their cancer treatment . Thus, transoral orthodromic temporalis muscle transfer was described for patients who were either unsuitable surgical candidates for or had chosen against more advanced facial reanimation surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the reasons underlying individual patients’ choice were complex and multifactorial, some did not want further open surgery for fear of surgical complications, unpredictability of results and prolonged recovery . In addition, an internal review demonstrated poorer clinimetric outcomes following facial nerve grafting in patients who went on to receive postoperative radiotherapy as part of their cancer treatment . Thus, transoral orthodromic temporalis muscle transfer was described for patients who were either unsuitable surgical candidates for or had chosen against more advanced facial reanimation surgery.…”
Section: Discussionmentioning
confidence: 99%
“…7 All histological diagnoses were confirmed with several pathologic tools as appropriated (immunohistochemistry, electron microscopy and molecular diagnosis) to exclude more frequent malignancies like sarcomatoid carcinoma and other mimickers. 8 We used descriptive statistics and inferential statistics with Cox's regression model and Kaplan-Meier test for survival analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the patients who have had this procedure at the same time as a decompression of their facial nerve have had symmetrical faces despite this having been done on one side. Nerve grafts, whether cable grafts, cross‐facial grafts or facial hypoglossal do not give better results than House–Brackmann grade III, which is far from normal . The advantage in muscle tone, position or movement provided by this procedure is thus useful.…”
Section: Discussionmentioning
confidence: 99%
“…After oncologic resections, nerve grafting and other reconstructive procedures should await definite free histological margins (Humphrey & Kriet, ). Postoperative radiotherapy is not a contraindication for facial reanimation procedure as clinical studies demonstrated that early postoperative radiation after interposition nerve grafting or after cross‐face nerve grafting was not a negative prognostic factor (Brown, Eshleman, Foote, & Strome, ; Leong & Lesser, ).…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative radiotherapy is not a contraindication for facial reanimation procedure as clinical studies demonstrated that early postoperative radiation after interposition nerve grafting or after cross-face nerve grafting was not a negative prognostic factor (Brown, Eshleman, Foote, & Strome, 2000;Leong & Lesser, 2013).…”
mentioning
confidence: 99%